Haunting Douglas & ghost dance Book and video reviews - Shennan, Jennifer (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Review of Douglas Wright's book and video. PALABRAS CLAVE: Douglas Wright, ghost dance, Royal New Zealand Ballet.
Dentro del apartado " Shelf Content".
Haunting Douglas. Video by Leanne Pooley, Spacific Films, 2003. Ghost Dance. Douglas Wright, Penguin Books (New Zealand), 2004.